2008
DOI: 10.1111/j.1349-7006.2008.00794.x
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer activity of RecQL1 helicase siRNA in mouse xenograft models

Abstract: Small interfering RNAs (siRNAs) are expected to have a medical application in human therapy as drugs with a high specificity for their molecular target mRNAs. RecQL1 DNA helicase in the human RecQ helicase family participates in DNA repair and recombination pathways in the cell cycle of replication. Silencing the RecQL1 expression by RecQL1-siRNA induces mitotic death in vitro specifically in growing cancer cells. By contrast, the same RecQL1 silencing does not affect the growth of normal cells, emphasizing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 33 publications
0
53
0
Order By: Relevance
“…Chronic or persistent activation of DNA damage signaling (in specific phospho-ATM) has an important role in elimination of tumor cells that undergo excessive DNA replication stress. 54 Consistently, it was reported that RECQ1 silencing has anticancer effects, and that RECQ1 is considered a new suitable target for cancer therapy 34,43,55 (Fig. 8).…”
Section: Discussionmentioning
confidence: 74%
“…Chronic or persistent activation of DNA damage signaling (in specific phospho-ATM) has an important role in elimination of tumor cells that undergo excessive DNA replication stress. 54 Consistently, it was reported that RECQ1 silencing has anticancer effects, and that RECQ1 is considered a new suitable target for cancer therapy 34,43,55 (Fig. 8).…”
Section: Discussionmentioning
confidence: 74%
“…A recently published study indicates that endogenous DNA damage that remains unrepaired in cancer cells due to RECQ1 silencing induces cancer cell-specific mitotic catastrophe. Those authors suggest that RECQ1 might play an important role in the regulation of mitotic cell death in cancer and that this helicase might be a suitable target for the development of new chemotherapeutic agents (63). Although much progress has been made and it is now clear that RecQ enzymes do not simply play redundant roles in cells, the challenge of understanding the unique cellular function of RECQ1 in HR or in other DNA metabolic processes is still open.…”
Section: Plasmid-based D-loops; a Role In Resolution Of Unproductive mentioning
confidence: 99%
“…However, the knockout mice seemed healthy and fertile (12). Two recent reports show that RECQ1 depletion using inhibitory RNA has anticancer effects in cells (14) and xenografts (15); this indicates that RECQ1 may be an important target for cancer therapy.…”
mentioning
confidence: 99%